2009
DOI: 10.1007/bf03216899
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming aboriginal knowledge at the cultural interface

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 8 publications
3
197
0
3
Order By: Relevance
“…It is important to understand that this framework acts as a starting point and may be changed to suit each school's needs according to the ways and processes of the local Aboriginal community. Intrinsic to these pedagogies are values, protocols, systems and processes that cannot exist unless there is a connecting synergy or collaborative interaction between Aboriginal and non-Aboriginal teaching staff (Yunkaporta, 2009). The underlying principles of the '8ways' of learning involve working out what our worldview is as a non-Aboriginal teacher given the historically incorrect teaching about the worldview of Aboriginal ways of knowing, as a science and a sustainable way of life for generations (ontology).…”
Section: Relevant Literaturementioning
confidence: 99%
“…It is important to understand that this framework acts as a starting point and may be changed to suit each school's needs according to the ways and processes of the local Aboriginal community. Intrinsic to these pedagogies are values, protocols, systems and processes that cannot exist unless there is a connecting synergy or collaborative interaction between Aboriginal and non-Aboriginal teaching staff (Yunkaporta, 2009). The underlying principles of the '8ways' of learning involve working out what our worldview is as a non-Aboriginal teacher given the historically incorrect teaching about the worldview of Aboriginal ways of knowing, as a science and a sustainable way of life for generations (ontology).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Cahill (1999), Malcolm et al (1999), and Cahill and Collard (2003), conversely, promoted the need for greater understanding of the utility of Aboriginal English in Australian classrooms in promoting learning. In addition, authors acknowledged the need for understanding of Aboriginal logical thinking, for example, "circular thinking" or "thinking the long way round", as documented by Yunkaporta and McGinty (2009). Further, several authors identified the imperative for acknowledging Aboriginality as an identity (or indeed, as many distinct and specific identities) as a critical necessity for establishing the recognition and respect required as a foundation for effective teaching practice (Christie, 1995;Jolly, 1995;Kerwin, 2011;Tripcony, 1994Tripcony, , 1995.…”
Section: Opinion Publicationsmentioning
confidence: 99%
“…These were discussed within the focus of cooperative-competitive, group-individual, and formal-informal organisational settings of classrooms. Many authors suggested that Aboriginal and Torres Strait Islander children tended to favour group collaboration rather than individually competitive settings (Bissett, 2012;Bond, 2010;Wemyss, 2003;Yunkaporta & McGinty, 2009). Suggestions were commonly made in the literature that students should negotiate task content, timelines, format, mode and classroom housekeeping (Bissett, 2012;Brogden and Kelly, 2002;Cahill, 1999;Colman-Dimon, 2000;Cresswell, Underwood, Withers & Adams, 2002;Hanlen, 2002).…”
Section: Practical Suggestionsmentioning
confidence: 99%
“…In producing this list of needs and strategies, the athletes were calling for Indigenous ways of knowing, being, and doing (Martin 2003;Yunkaporta 2009) both during sport and beyond.…”
Section: Ii)mentioning
confidence: 99%